Paul Ricoeur e a Questão Política / Paul Ricouer and the Political Question - Portier, Philippe (Numen, 2012)
Resumo texto visa colocar em destaque a dimensão política na obra filosófica de Paul Ricoeur. Examinando a política dentro de sua dinâmica ambivalente - “emancipadora” e “subjugadora” -, a perspectiva de Ricoeur busca confrontar a violência do poder com as esferas da “palavra” e da “racionalidade”. Racionalidade não identificada com eficácia, mas com ética. Entremeado com referências à participação de Ricoeur no movimento do Cristianismo social e na Federação Protestante de Ensino, o artigo destaca que uma das preocupações do filósofo na sua buscapor um projeto de institucionalização democrática foi a “educação para a tolerância religiosa”. Palavras-Chave: Filosofia; Palavra; Racionalidade; Tolerância Religiosa. Abstract The text aims to highlight the political dimension in the Paul Ricoeur’s philosophical work. By examining politics within its ambivalent dynamics - “liberating” and “subjugating” - the Ricoeur’s perspective seeks to contrast the violence of power with the spheres of “word” and “rationality”. Rationality is not identified with efficiency, but with ethics. Interwoven with references to Ricoeur’s participation in the movement of social Christianity and the Protestant Federation of Education, the article points out that one of the concerns of the philosopher in his quest for a democratic process of institutionalization was the “education for religious tolerance”. Keywords: Philosoph; Word; Rationality; Religious Tolerance.